The Influence Of Employee Competence And Work Motivation On Employee Performance At The Sikap Dalam Subdistrict Office In Empat Lawang Regency - Gibran, Ahmad; Anggriani , Ida; Fitriano , Yun (Journal of Applied Financial Management, 2025)
This study aims to determine the effect of competence and motivation on employee performance at the Sikap Dalam Subdistrict Office in Empat Lawang Regency. The independent variables in this study are competence and motivation, while the dependent variable is employee performance. A Likert scale was used to measure the indicators of each research variable. The population in this study was all employees of the Sikap Dalam Subdistrict Office in Empat Lawang Regency. The sample size used in this study was 37 respondents. Data analysis used multiple linear regression tests, with the F test used to determine the combined effect of competence and motivation on employee performance, while the t test was used to determine the separate effects of competence and motivation on employee performance. The results of the analysis show that competence and work motivation simultaneously have a significant effect on employee performance. The partial test results show that competence and work motivation have a significant effect on employee performance. Motivation has a more dominant effect on employee performance compared to competence. The effect of motivation, at 42.7%, plays a more dominant role in improving employee performance compared to the competence factor, at 38.5%.